1979
DOI: 10.1063/1.438750
|View full text |Cite
|
Sign up to set email alerts
|

The AX system of Ni2 in argon matrices

Abstract: A new, fully ab initio investigation of the ArNO (X 2 Π) system. II. Bound states of the Ar-NO complex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The data describing these curves are in Table 2 . GVVPT2 predicted the ππ–hole states to lie higher in energy than the δπ–hole states, in agreement with previous studies ( Ahmed and Nixon, 1979 ; Rasanen et al, 1987 ; Russo et al, 1994 ). For all four δπ–hole states studied, the major CSFs involved a doubly occupied 4sσ g bonding orbital.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The data describing these curves are in Table 2 . GVVPT2 predicted the ππ–hole states to lie higher in energy than the δπ–hole states, in agreement with previous studies ( Ahmed and Nixon, 1979 ; Rasanen et al, 1987 ; Russo et al, 1994 ). For all four δπ–hole states studied, the major CSFs involved a doubly occupied 4sσ g bonding orbital.…”
Section: Resultssupporting
confidence: 90%
“…The 1 1 Σ u - state, which was predicted as the ground state of Ni 2 at the ACPF level of theory ( Cheskidov et al, 2012 ) and found to lie quite close to a 1 Σ g + ground state in a limited CI study ( Ahmed and Nixon, 1979 ), was found at the GVVPT2 level to lie 91.09 cm −1 above the X 1 Γ g state at equilibrium. The 2 1 Σ u - state, however, lay much higher energetically (18,575.76 cm −1 above the ground state at equilibrium).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…[66][67][68][69][70][71][72][73][74] The experimental bond distance for the Ni 2 molecule is 2.1545± 0.0004 Å. The nickel dimer is one of the most experimentally studied nickel clusters.…”
Section: Nimentioning
confidence: 99%
“…The electronically excited states are difficult to assign, but appear at wavelengths o450 nm. 34 The UV-vis spectra of Ni 2 shows several absorption bands at B3 eV. 35,36 The ds gpp u ( 3 p u or C state) is strongly bound, but overlaps with the dissociative ss gss u ( 3 S u À or B state).…”
Section: Resultsmentioning
confidence: 99%